Numerical Methods and Implementation in Geotechnical Engineering - Part 2 - Cheng, Y. M. (Frontiers in Civil Engineering Ser., 2020)
Numerical Methods and Implementation in Geotechnical Engineering explains several numerical methods that are used in geotechnical engineering. The second part of this reference set includes more information on the distinct element method, geotechnical optimization analysis and reliability analysis. Information about relevant additional numerical methods is also provided in each chapter with problems where applicable. The authors have also presented different computer programs associated with the materials in this book set which will be useful to students learning how to apply the models explai.